Should Bone Bruising be Considered as A Fracture in Medicolegal Process A Case Report - Gürbeden, Burçin; Özkan, Devrim Sertaç; Özdemir, Mehmet Hakan (The Bulletin of Legal Medicine, 2016)
Bone bruising is a microtrabecular fractures characterized with edema, hemorrhage and irregularity occured in subcondral area of bone. Because of that it is limited with medulla, it can’t be detected by direct graphies. Magnetic resonance imaging (MRI) is important in diagnosis. In our case, our patient is a 23 years old male, he hit his right knee to the front console of car in atraffic accident, he was discharged from a university hospital after medical follow up, in MRI after 1 month later because of that his pain didn’t heal, intratrabecular irregularity in a diffuse patchy pattern and areas of intramedullary bone marrow edema were determined in distal 1/3 of femur. Focal intramedullary bone marrow edema determined in subcondral face of lateral tibia. In this study, it was aimed to attract attention to a concept that diagnosed as a bone bruising in distal of right femur by MRI examination and don’t take place in guide of “Evaluation of Injuries Defined In Turkish Criminal Code” and to suggest a new evaluation criteria to the guide. Keywords: Bone Fracture, Bone Bruise, Medikolegal Assessment.